Arbitrase Solusi Alternatif Dalam Menyelesaikan Sengketa Ekonomi Syariah - Putro Santoso, M. Alif Eko (TAQNIN: Jurnal Syariah dan Hukum, 2025)
Sharia economic disputes are conflicts arising from different interpretations of rights and obligations in agreements based on sharia principles, which are often caused by a lack of transparency in the contract. This article discusses the definition, causes, classification, and resolution of sharia economic disputes in Indonesia. This dispute resolution process is governed by applicable law, particularly by the Religious Courts, which have the authority to examine and resolve sharia economic cases in accordance with Law No. 3 of 2006. Settlement can be done through litigation, which includes simple lawsuits and ordinary procedures, or through non-litigation channels such as alternative dispute resolution (APS) and arbitration. APS encourages amicable settlement with the principle of deliberation, while arbitration involves the appointment of an arbitrator to resolve the conflict. This article emphasizes the importance of maintaining sharia principles in the entire dispute resolution process, both through litigation and non-litigation channels, in order to achieve justice and sustainability in the Islamic economy. And the method used is normative juridical to analyze the laws and regulations governing sharia economic dispute resolution. The results of the discussion obtained are that settlement through arbitration is the settlement most often used by the parties to the dispute because the process in arbitration is more efficient and cost-effective and has strong legal certainty.